Associations Between Endoscopic Primary Prophylaxis and Rebleeding in Liver Cirrhosis Patients with Esophagogastric Variceal Bleeding - Gao, Yanying; Yuan, Haixia; Han, Tao; Zhang, Xu; Li, Fenghui; Tang, Fei; Liu, Hua (Frontiers in Surgery, 2022)
Aim: To identify the association of endoscopic primary prophylaxis and the risk of rebleeding in patients with liver cirrhosis receiving endoscopic therapy. Methods: This cohort study involved in 944 liver cirrhosis patients with esophagogastric variceal bleeding (EGVB) receiving endoscopic therapy. All participates were divided into the rebleeding group (n=425) and non-rebleeding group (n=519) according to the occurrence of rebleeding in patients. Rebleeding indicated any bleeding after endoscopic therapy for the first bleeding in esophagogastric varices in liver cirrhosis patients. Univariate and multivariate logistic analyses were employed to identify the association of endoscopic primary prophylaxis and rebleeding in patients with liver cirrhosis after endoscopic therapy. Results: In total, 425 patients rebleeded in patients at the end of the follow-up. The risk of rebleeding in patients with endoscopic primary prophylaxis was decreased by 0.773 times (OR=0.227, 95%CI: 0.139-0.372, P<0.001) after adjusting covariables. Subgroups were divided according to the Child-Pugh (CP) score and the results revealed that the risk of rebleeding in patients with endoscopic primary prophylaxis was decreased by 0.858 times in Grade A patients (OR=0.142, 95%CI: 0.066-0.304, P<0.001) and 0.804 times in Grade B patients (OR=0.196, 95%CI: 0.085-0.451, P<0.001) compared with patients without endoscopic primary prophylaxis, but showed no difference in Grade C patients. Conclusion: Endoscopic primary prophylaxis was associated with a decreased risk of rebleeding in liver cirrhosis patients with EGVB after endoscopic therapy, which suggested that clinicians should pay more attention on endoscopic primary prophylaxis to prevent the occurrence of rebleeding in liver cirrhosis patients with EGVB.